Strategi Komunikasi Pemasaran Digital: Mengoptimalkan Uniqueness untuk Mempertahankan Loyalitas Pelanggan - Felix, Antonius; Cerlysia, Cerlysia; Sheng, Liu De; Hendra, Martin; Tjalani, Ricky; Colin, Vincent (Jurnal Common, 2023)
This research focuses on the digital marketing communication strategy implemented by SPBU Shell in Jakarta, with a specific emphasis on the analysis of Customer Experience in the Gas Station Industry. Using a qualitative approach and observation, this study aims to understand aspects related to customer experience at SPBU Shell. The literature review includes a review of scientific and technical literature related to Customer Experience at SPBU Shell. Data sources consist of internal documents from Shell, company policies, and official information from Shell. By applying thematic analysis and information synthesis, this research develops a holistic understanding of Customer Experience at SPBU Shell, with a focus on digital marketing communication strategies. The research results are expected to provide valuable insights to strengthen Shell's position in the competitive market by highlighting the uniqueness of services and effective digital strategy implementation. Shell's success in designing this approach creates emotional bonds with customers, strengthens brand image, and enhances customer engagement through integrated digital platforms, engaging multimedia content, direct interactions via social media, educational content, special promotions through the app, influencer marketing, targeted online campaigns, reputation management, and data analysis. This digital marketing approach not only maintains but also enhances Shell's position in an increasingly competitive market.